STRATEGI MANAJEMEN PEMBIAYAAN DALAM MENGELOLA DANA BEASISWA DI STAI ALI BIN ABI THALIB SURABAYA - Dani, Dani ElMuslim; Imelda Dian Rahmawati (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study analyzes financing management strategies in managing scholarship funds at STAI Ali bin Abi Thalib Surabaya. Scholarships are considered crucial as instruments of educational equity and as means to improve the quality of human resources, particularly for outstanding students and those from underprivileged backgrounds. The research employed a descriptive qualitative approach through interviews, observations, and documentation involving the Vice Chairman III for student affairs, scholarship managers, and scholarship recipients. Data were analyzed using the interactive model of Miles & Huberman, which includes data reduction, presentation, and verification. The findings reveal that financing management strategies consist of: (1) need-based budget planning with systematic recording in accordance with Islamic principles, (2) transparent recipient selection based on academic achievement, Qur’an memorization, leadership training, and economic background, (3) fund distribution through direct campus payments or student bank transfers, and (4) periodic academic and financial evaluations. These strategies have been proven to enhance learning motivation, academic performance, reduce dropout rates, and encourage student involvement in campus organizations. Overall, accountable and professional scholarship management contributes significantly to expanding access, improving quality, and ensuring the sustainability of higher education. This study also emphasizes the importance of innovation in financing management, particularly in transparency, student financial literacy, and sustainable funding sources, so that scholarship programs can continue and provide long-term benefits